2019
DOI: 10.1371/journal.pgen.1008362
|View full text |Cite
|
Sign up to set email alerts
|

The quorum sensing transcription factor AphA directly regulates natural competence in Vibrio cholerae

Abstract: Many bacteria use population density to control gene expression via quorum sensing. In Vibrio cholerae, quorum sensing coordinates virulence, biofilm formation, and DNA uptake by natural competence. The transcription factors AphA and HapR, expressed at low and high cell density respectively, play a key role. In particular, AphA triggers the entire virulence cascade upon host colonisation. In this work we have mapped genome-wide DNA binding by AphA. We show that AphA is versatile, exhibiting distinct modes of D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 63 publications
(98 reference statements)
0
30
0
Order By: Relevance
“…Little is known about vchM regulation but it was recently shown that the V . cholerae quorum sensing low density transcriptional regulator AphA is able to bind the vchM region [ 55 ] leaving the possibility that vchM may be regulated by quorum sensing. Moreover, vchM was previously found to be differentially expressed between different stages of human infection [ 56 ], suggesting the possibility that modulation of cytosine methylation levels can be adaptative during V .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about vchM regulation but it was recently shown that the V . cholerae quorum sensing low density transcriptional regulator AphA is able to bind the vchM region [ 55 ] leaving the possibility that vchM may be regulated by quorum sensing. Moreover, vchM was previously found to be differentially expressed between different stages of human infection [ 56 ], suggesting the possibility that modulation of cytosine methylation levels can be adaptative during V .…”
Section: Discussionmentioning
confidence: 99%
“…Haycocks et al mapped global binding of the TF AphA, expressed at low cell density, and found that it activated the virulence cascade during colonisation as well as repressing natural competence. The latter is controlled by the TF HapR under high cell density and as such the study identified a mechanism by which V. cholerae directly regulates the marine-to-host lifestyle switch [86].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 94%
“…Regarding QS, we observed that genes known to be activated or inhibited by AphA [27,28] in V. cholerae are, respectively, up-and downregulated by TOB in hapR+ strain (Figure 3A), suggesting activation of the AphA low cell density regulon upon TOB treatment. In V. cholerae, the level of AphA protein is known to be negatively controlled by the concerted action of AI-2, CAI-1 and DPO (an autoinducer that is part of a third QS pathway in V. cholerae [29]), with AphA being barely detectable upon the simultaneous presence of these autoinducers [30].…”
Section: Tob Influences Qs Response Of V Cholerae and Interferes With Ai-2 Signaling Of Photorhabdus Luminescensmentioning
confidence: 99%